1-Naphthyl quinoxalin-2-yl ether - Hassan, N.D.; Tajuddin, H.A.; Abdullah, Z.; Ng, S.W. (International Union of Crystallography, 2009)
In the crystal structure of the title compound, C(18)H(12)N(2)O, the dihedral angle between the two fused-ring systems is 84.3 (1)degrees; the C-O-C angle at the ether O atom is 117.31(18)degrees.